Finite element design sensitivity analysis and its integration with numerical optimization techniques for structural design - Kumar, V.; Lee, S.-J.; German, M.D. (Computers & structures, 1989)
This paper presents the development of a structural design optimization methodology and a software system DESIGN-OPT by integrating numerical optimization techniques, finite element methods, and pre- and post-processing CAE tools. Specifically, the commercially available codes COPES/ADS and ADINA are employed for numerical optimization and finite element analysis, respectively; and software packages like MOVIE.BYU, PLOT 10 and SUPERTAB are used for pre- and post-processing purposes. The finite-difference and semi-analytical (or implicit differentiation) approaches of design sensitivity analysis were explored with the ADINA code for static as well as dynamic problems; and a comparison of the two approaches is made in terms of computational efficiency, solution accuracy and the ease of software implementation. A broad range of element types (truss, beam, plate and 2D/3D continuum) are considered, and the effects of centrifugal and thermal loadings are included. A number of interface programs are developed to integrate various computer codes: for example, OPT-AN and AN-OPT processors transfer data between the optimizer and the analyzer. A variety of design problems related to both size and shape optimization are presented as illustrative examples. Finally, some remarks are made for further research on the subject, such as the role of geometric modeling and automatic meshing for shape optimization.